Health literacy and online pharmacy adoption by Saudi population using UTAUT - Amal K. Suleiman (International Journal of Data and Network Science)
The field of online pharmacies is expanding rapidly and has become a crucial component in delivering pharmaceutical services across Saudi Arabia. This study aims to explore the factors influencing the adoption of online pharmacies by the Saudi population, utilizing an enhanced version of the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. This study employed a cross-sectional design, utilizing an online questionnaire that was pre-validated and shared via social media channels between August 2024 and October 2024. The study focused on Arabic-speaking individuals aged >18 years. The gathered data were examined through structural equation modeling (SEM) using AMOS software (v.22.0). The study found that the UTAUT model demonstrates strong applicability in explaining the adoption of online pharmacies, accounting for 62.4% (R² = 0.624) of the variance in behavioral intention. Among the key factors, effort expectancy (p < 0.001) emerges as the most influential predictor of behavioral intention, followed by facilitating conditions (p < 0.001) and health literacy (p < 0.001). However, the analysis reveals that perceived risk (p > 0.05) and personal innovativeness (p > 0.05) do not have a statistically significant impact on behavioral intention. The study results would help formulate more effective strategies for establishing online pharmacy operations in developing nations like Saudi Arabia. This study contributes to enhancing the traditional UTAUT model through the integration of additional factors such as health literacy, personal innovativeness, perceived risk, and perceived trust. These variables introduce new dimensions to the existing literature on online pharmacies.